Analisis Tingkat Keuntungan Modal Sendiri Pada Bank Pemerintah (Persero) Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Pertama Wiko Setiyawan; Sukasmanto Sukasmanto (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2014)
Performance measurement of banking management becomes a major problem for the bank. One measure of a bank's performance is return on equity (ROE). Theoretically, the ROE is influenced by variables Operating Expenses to Operating Income (BOPO), Net Profit Margin (NPM), Loan to Assets Ratio (LAR).This study aims to find empirical evidence of the influence of these variables to ROE. This research was conducted at the state banks (Persero) listed in Indonesia Stock Exchange (IDX) in the period 2003 until 2012 with purposive sampling technique. Selected samples are Bank Mandiri, Bank Rakyat Indonesia (BRI), and Bank Negara Indonesia (BNI). Tests performed with the classical assumption and hypothesis testing with multiple regression analysis to examine the effect of variable BOPO, NPM, and LAR on Return on Equity (ROE).The test results indicates that the assumptions of classical regression model, the dependent variable and independent variables escaped classical assumption. The results of data analysis indicates that the variable BOPO has a negative effect and is not significant to ROE. NPM has a positive and significant effect to ROE. While, LAR has a positive effect but is not significant to ROE. But simultaneously BOPO, NPM, and LAR significant effect on ROE. The results of this study are expected to be relied upon, either by the management of the bank to improve its financial performance as well as by investors in determining investment strategy.